Conflict, security and development : an introduction - Beswick, Danielle; Jackson, Paul, 1968 April 24- (New York, NY : Routledge, 2015)
'This textbook draws on academic theory, field research and policy developments to provide an overview of the connections between security and development, before, during and after conflict. This 2nd edition is revised and updated to take account of changes that have occurred in both policy and academic arenas which are relevant to students and practitioners in this area. In an interdependent world it is often argued that the challenges of underdevelopment and insecurity have global implications. This textbook charts an accessible course through these complex debates, providing a comprehensive introduction for those encountering these issues for the first time. The main aims of the revised edition are: - to set out how thinking on conflict, security and development has changed over time and continues to evolve; - to explore the consequences of these changes, particularly for the theory and practice of development and security promotion; - to introduce a range of case studies from across the globe, in order to explore the implications of a combined approach to security and development. The authors are experienced in both the theory and the practice of this field, and illustrate the links between conflict, security and development with practical examples, drawing on key case studies from the past twenty years. Each chapter is informed by student pedagogy and the book will be essential reading for all students of development studies, war and conflict studies, and human security and is recommended for students of international security and IR in general'--
Includes bibliographical references : pages 207-221 and index.
Keywords: Security, International; Political violence -- Economic aspects; Economic development -- Political aspects